O estilo Cristina Fernández de Kirchner (2007-2011) - Silva, Vera Lucia Correa da (Meridiano 47 - Journal of Global Studies, 2017)
This article aims to analyze the style kirchnerista in Argentina's foreign policy focusing on the main agenda of the government of Cristina Fernandez de Kirchner (2007-2011) to the United States, Brazil and MERCOSUR.